IMPLEMENTASI ALGORITMA NAIVE BAYES PADA SISTEM MONITOR KUALITAS AIR KOLAM LELE BERBASIS IOT - Setiono, Nur Syahad; Utomo, Yudo Bismo; Alfin, Ach Arif (Electro Luceat, 2024)
In catfish farming, water quality stability is a key factor as it is considered a crucial parameter for successful catfish cultivation. Several factors influence the pond water quality, such as leftover food, accumulated fish waste, and environmental conditions like rainy or dry seasons. Typically, the replacement of pond water is determined based on visual cues such as water color and odor, relying on rough estimates. Therefore, the author chose the title "Implementation of Naive Bayes Algorithm in IoT-Based Catfish Pond Water Quality Monitoring System" to design a monitoring system capable of assessing the quality of catfish pond water. This system includes monitoring parameters such as temperature, pH, turbidity, and pond water status through the internet network, with the results being displayed on an LCD screen and a website. The Naive Bayes algorithm is employed to determine the status of catfish pond water using data collected from sensors. The research findings indicate a 40% decrease in catfish mortality in ponds equipped with IoT-based systems.